Dense high-entropy boride ceramics with ultra-high hardness. (15th April 2019) - Zhang, Yan; Guo, Wei-Ming; Jiang, Ze-Bin; Zhu, Qi-Qi; Sun, Shi-Kuan; You, Yang; Plucknett, Kevin; Lin, Hua-Tay
Abstract: Highly dense high-entropy boride ceramics with ultra-high hardness were prepared by spark plasma sintering of the self-synthesized high-entropy boride powders. High-entropy boride compounds of (Hf0.2 Zr0.2 Ta0.2 Cr0.2 Ti0.2 )B2, (Hf0.2 Mo0.2 Zr0.2 Nb0.2 Ti0.2 )B2 and (Hf0.2 Mo0.2 Ta0.2 Nb0.2 Ti0.2 )B2 with some oxide impurities were obtained by borothermal reduction at 1600 °C. The yield of the samples after sintering was improved to be 97.2 wt%, 92.8 wt% and 97.6 wt%. The densification and hardness of the high-entropy boride ceramics were remarkably enhanced after sintering the as-obtained powders at 2000 °C. The relative density of Hf0.2 Zr0.2 Ta0.2 Cr0.2 Ti0.2 ceramics was 99.2% and the hardness achieved a value up to 28.3 ± 1.6 GPa, which was significantly higher than reported values. Graphical abstract: Unlabelled Image